(3cTa GdCSQGQ Yf Yde GdZHGQs - (3GdbdUGOj , CHh GdMSf,J (B891 (3g` s ((3ehQjJGfjG s)
(3ChdgG (B:s
(3CeG HYO agPg fHPg cGajg TGajI hYf LGfH GdENdGd hGdEedGd eJLGajI hSejJI cTa GdCSQGQ Yf Yde GdZHGQ hef Gddg CSCd GdEYGfI hGdEQTGO Edi ShGA GdWQjb s
(3BNQgG (B:s
(3hCLeYg Edi KdGKg hZdi SJI ahbgG JNQL dc YTQI CjVkG bVY GdUaQ hgPg ahb GdNW GLeY KdGKI hYTQjf hCQHY eGFI Edi NeSI hSJjf heGFJjf s
(3eNWhWI eJBcdI GdCWQGas
(3GdeNWhW eQbe GdUaMGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B10 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B230s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B355s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMQha h GdChaGbs